2017
DOI: 10.1177/0886260517701451
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Domestic Violence Advocates’ Responses to Reproductive Coercion

Abstract: Reproductive coercion (RC) is a form of intimate partner violence (IPV) that continues to lack adequate attention by both researchers and practitioners. RC is defined as "male partners' attempts to promote pregnancy in their female partners through verbal pressure and threats to become pregnant (pregnancy coercion), direct interference with contraception (birth control sabotage), and threats and coercion related to pregnancy continuation or termination (control of pregnancy outcomes)." This type of partner vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…In this connection, it is important to distinguish between the relationship dysfunction and violent entrapment or "battered woman syndrome" including the learned helplessness [44,45]. RC is regarded to be a form of IPV; it can lead to unintended pregnancy, abortion, poor pregnancy outcomes, STI, psychological trauma and depression [2,3,46,47]. Among potential contributing factors are disrespect for laws and regulations, impunity of some offenses and offenders, habitual display of death and violence on TV indirectly trivializing less spectacular phenomena such as the IPV, sexual and reproductive coercion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection, it is important to distinguish between the relationship dysfunction and violent entrapment or "battered woman syndrome" including the learned helplessness [44,45]. RC is regarded to be a form of IPV; it can lead to unintended pregnancy, abortion, poor pregnancy outcomes, STI, psychological trauma and depression [2,3,46,47]. Among potential contributing factors are disrespect for laws and regulations, impunity of some offenses and offenders, habitual display of death and violence on TV indirectly trivializing less spectacular phenomena such as the IPV, sexual and reproductive coercion.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive coercion (RC) interferes with a woman's decisionmaking regarding reproductive health; it may consist of contraception sabotage and/or pressure to either carry a pregnancy to term or to have an abortion [1]. The RC definitions include male partners' attempts to promote pregnancy through verbal pressure and threats [2]. The contraception sabotage includes hiding, withholding or destroying contraceptives, deliberate tearing or removing of condoms or failing to withdraw in an attempt to induce pregnancy despite a female partner's wishes to prevent the pregnancy [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most research about RC to date has focused on healthcare settings IJCJ&SD 3 www.crimejusticejournal.com (Fleury-Steiner and Miller 2019;Tarzia et al 2019a;Tarzia et al 2019b). One US study explored the extent to which DV advocates proactively and/or reactively addressed RC with women accessing DV victim services (McGirr et al 2017). This study found that despite low levels of discomfort when discussing topics related to RC and minimal barriers to discussing it, few advocates regularly addressed the topic.…”
Section: Introductionmentioning
confidence: 99%
“…This study found that despite low levels of discomfort when discussing topics related to RC and minimal barriers to discussing it, few advocates regularly addressed the topic. McGirr et al (2017) recommended universal education to every client, with discussions covering typical coercive behaviours, emergency contraception, pregnancy testing, contraception that can be used without a partner's knowledge as well as checking that pregnant survivors feel safe to decide about their pregnancies. As little is known about how support workers and lawyers respond to disclosures of RC we explore the issue in the following sections of this article.…”
Section: Introductionmentioning
confidence: 99%
“…RC is defined e.g. as male partners' attempts to promote pregnancy through verbal pressure and threats (pregnancy coercion), direct interference with contraception (birth control sabotage), threats and coercion related to pregnancy continuation or termination (control of pregnancy outcomes) [1]. Contraception sabotage includes hiding, withholding, destroying, or removing female-controlled contraceptives or deliberately breaking or removing a condom during sex or failing to withdraw in an attempt to promote pregnancy despite a female partner's wishes to prevent pregnancy [2].…”
Section: Introductionmentioning
confidence: 99%